Cell Death and Exosomes Regulation After Myocardial Infarction and Ischemia-Reperfusion - Wu, Xun; Iroegbu, Chukwuemeka Daniel; Peng, Jun; Guo, Jianjun; Yang, Jinfu; Fan, Chengming (Frontiers in Cell and Developmental Biology, 2021)
Cardiovascular disease (CVD) is the leading cause of death in the global population, accounting for approximately one-third of all deaths each year. Most of these cases manifest as myocardial infarction (MI) or cardiac arrhythmia caused by myocardial ischemia, which occurs when the blood flow to the heart is reduced and the heart tissue is damaged. In the process of MI or myocardial ischemic-reperfusion (I/R) injury, both regulated and nonregulated cell death methods are involved. The key factor for the prognosis of the patients is the size of the infarct area, which determines the survival of myocardial cells. Cell therapy for MI has been a research hotspot in recent years, but due to its shortcomings, such as immunogens, exosomes secreted by cells have attracted increasing amounts of attention. Exosomes are extracellular vesicles containing biologically active substances, such as lipids, nucleic acids, and proteins. New evidence suggests that exosomes play a key role in the regulation of cell death after MI. Exosomes from a variety of cells can participate in the cell damage process after MI and rescue the damaged myocardium. Therefore, in this review, we focus on introducing various cell-derived exosomes to reduce cell death after MI by regulating the cell death pathway to better understand the mechanism of myocardial repair and to provide a reference for clinical treatment.